Aerodynamic measurement-Maximum Phonation Time in young patients with benign vocal fold lesions and with normal voice: a comparative analysis - Dar, Nisar Hussain; Ahmad, Mukhtar; Lone, Zubair A.; Patigaroo, Suhail Amin (International Journal of Research in Medical Sciences, 2019)
Background: Clinicians use Maximum Phonatory Time (MPT) as one of tool to verify the glottic efficiency objectively. Impairment of vocal fold mucosa integrity due to lesions results in alteration in MPT. The aim of current study was to compare MPT in young adults with vocal fold lesions and age and sex matched normal subjects. Methods: This study was conducted in the Department of ENT & Head and Neck surgery of Government Medical College Srinagar on 41 adult patients with benign vocal fold lesions and 41 healthy subjects matched for age and sex for a period of 2 years from April 2017- April 2019. The aerodynamic measure was measured as maximum phonation time in seconds and the results were analysed statistically. Both patients and controls were explained the procedure. Results: Mean MPT in seconds in males with vocal fold lesion was 14.42 seconds with SD of 5.62 seconds and in females was 10.81 seconds with SD of 3.44 seconds. Coefficients of variation (CV) was 0.35 and 0.21 respectively. In control group it was 18.15 seconds with SD of 5.88 in males and in females it was 15.72 seconds with a SD of 6.21. Mean difference between patients and controls in males and females was 3.8 and 4.9 respectively. P-Value in males and females was 0.053 and 0.003 respectively. Conclusion: Vocal cord lesions decrease MPT in both sexes even in young adults.